Optimization of microwave heating on orange sacs products. Issue 1 (June 2020) - Wang, Jun; Li, Guijie; Cheng, Yujiao; Huang, Linhua; Sun, Rongrong; Wu, Houjiu
Abstract: Various applications of microwave have been put into effect in the field of food processing. The microwave assisted thermal sterilization (MATS) was of great significance because of its less time consuming and higher efficient. In this paper, response surface methodology was used to optimize the process. The sterilization of orange sacs was potimiazed using by response surface methodology (RSM). The optimal processing parameters of MATS on orange sacs are as follow: microwave power, 6 kW, microwave sterilization time, 350 s, amount of orange sacs, 4500 g. Sterilized under this condition by MATS, orange sacs only maintained 3.7 CFU lethal magnitude which was consistent with the standards requirement. The key factor in the response surface using microwave sterilization and the interaction between them were also determined and discussed which could make it evident that MATS should be an idea candidate in the sterilization of some fruit or vegetable products as ready to eat. From these results, the best conditions of microwave sterilization are power 6kw, microwave sterilization time 350s and material quantity 4500g.